Effect of crude extract of genipap (Genipa americana) on the control of the bovine tick Rhipicephalus (Boophilus) microplus (Research, Society and Development, 2020)
Tick is the most important ectoparasite among cattle, being favored by the climatic characteristics of Brazil. This parasite commits herds causing disease, stress, allergic reactions and damage to the animal's hide. Due to the successive uses of synthetic acaricides, ticks have developed resistance to these chemicals, leading to research with natural products with the same acaricidal effect. The present study aimed to analyze the effect of crude extract of genipap on the control of R. microplus. The methodology used for the acaricidal efficiency was the immersion test of engorged tick females, in concentrations of 50, 75, 100, 150 and 200 mg mL-1, diluted to a proportion of ethanol and water (70:30), for the positive control used Fipronil and the negative control used only the diluent. The effect on acetylcholinesterase inhibition was evaluated using the in vitro Ellman microplate test. It was observed that the efficiency of the product in all treatments (50 to 200 mg mL-1) had an acaricidal effect against R. microplus, with averages ranging from 64.04 to 99.22%, respectively. With the crude extract it was not possible to observe the inhibition of acetylcholinesterase (5.18%), however, fraction 2 of the extract partition showed an inhibition of 67.4%, demonstrating to have substances capable of inhibiting the enzyme. The crude extract of genipap has shown to be efficient in the control of the bovine tick and must be studied to be part of a strategic ecological control.